An exploratory study of women prisoners' attitudes towards their self-harm and the use of medical skin camouflage. Issue 1 (2nd January 2019) - Gutridge, Kerry; Dunlop, Brendan J; Patterson, Megan; Mitchell, Heather; Philbin, Jennifer; Walker, Tammi; Ranote, Sandeep; Robinson, Louise; Abel, Kathryn M
ABSTRACT: Self-harm is a growing problem in UK prisons with women self-harming more than men. Self-harm can leave permanent scarring. Research on scarring suggests that living with scars can lead to psychological difficulties; however, there is little research on the specific effects of self-harm scars. Medical skin camouflage (MSC) can be used to cover numerous skin conditions. The use of MSC for women in prison with self-harm scars has not been examined previously. A focus group involving 10 women prisoners aimed to (1) explore feelings about self-harm scars, (2) examine effects that scars have on life in prison and (3) examine thoughts on using MSC in prison. This group formed part of a larger project designed to test the feasibility and acceptability of MSC for women who self-harm in prison. A topic guide was created with two service user researchers with experience of self-harm in prison. The results have been divided into three themes: (1) feelings about self-harm scars, (2) covering self-harm scars and (3) attitudes towards MSC. Our findings indicate that women in prison tend to feel embarrassed and self-conscious about their scars, and the presence of scars affects their relationships within prison. The women were enthusiastic about MSC, suggesting that it has the potential to affect women's well-being and ability to engage with others.